PENINGKATAN KREATIVITAS ANAK MELALUI METODE BERMAIN MEDIA PLAYDOUGH DI KB MATAHARI KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA PADA TAHUN AJARAN 2016/2017 - Fitriyana - Fitriyana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
Early age is a good time to lay the foundations of physical, linguistic, emotional, social, self-concept, art, moral and religious values. This study aims to determine the improvement of children's creativity through playdough media play methods in the play group Matahari Kecamatan Muara Badak Kabupaten Kutai Kartanegara in the academic year 2016 / 2017. The subject of this study consisted of ten children, five boys and five girls in Group Play Matahari Kecamatan Muara Badak Kabupaten Kutai Kartanegara in the academic year 2016 / 2017. The object of research is Child Creativity. This study was conducted two cycles with each stage of planning, implementation, observation, and reflection. Data collection techniques used are observation and documentation. Data analysis technique is descriptive analysis of quantitative and qualitative. The results of research in this study the increase percentage average completeness of the achievement of creativity. Child creativity on Pre-action; the child who achieves the indicator Grows Up Expectations and Grows Very Good is 20% to 50% in cycle one and after some improvements in cycle two reaches 80% or eight children out of ten children has achieved Evaluating Growth Indicator and Growing Very Good. The success is done with the steps (1) The teacher always gives motivation to the students to be active and excited either by applause or by singing (2) the teacher gives positive reinforcement to the child (3) the researcher teaches by giving oral praise so the child motivated and felt appreciated. From this research, it can be concluded that the use of Playdough Media Play method can improve children creativity in play group Matahari Kecamatan Muara Badak Kabupaten Kutai Kartanegara in 2016/2017 academic year.